HUBUNGAN STIGMA DIRI DENGAN KEPATUHAN MINUM OBAT ARV PADA ORANG DENGAN HIV/AIDS (ODHA) - Mizam Ari Kurniyanti; Wira Daramatasia (Jurnal Ilmiah Kesehatan Media Husada, 2021)
Human immunodeficiency virus/Acquired immunodeficiency syndrome (HIV/AIDS) Is one of the worst pandemic, besides impact to the physical cause psikososial anciety.Until now it has not been found the drug therapy / the healer HIV / AIDS so as to cause odha feel down even apathetic, in addition condition self stigma (perceived stigma) in ODHA so can be lowered compliance drink ARV. The purpose of research carried out in peer support groups jombang care center ( kds jcc ) district jombang in general to drink in compliance ARV ODHA .In this research using analytic methods the cross sectional. Observasional respondents were 55 ODHA taken purposive approach based on techniques of sampling of 550 ODHA joined at KDS JCC and meet the criteria for inclusion and ekslusi. The self stigma measured with selected berger stigma scale and drink ARV measured by of the questionnaire was compliance drink a drug ( MMAS ). Data analyse using Somer’s test. the results of the study obtained as follows 61,8% Male ODHA respondent, 78,2% in age 26 year until 45 year, 43,6% Senior High Shool, 67,3% work, 45,5% had income levels under 1 million per month, 47,3%, married and 72,5% had diagnose HIV/AIDS in 1 until 5 years. Perceived stigma from the perception of living most enough as much as 74,5%. Compliance drink were any ARVS in ODHA 56,4% categorized as high compliance .There is a significant relation exists between / meaningful stigma to compliance drink were any ARVS (p=0,024 dan r= 0,276). Advice the strategy koping who focuses on the problem ( problem-focused coping strategies ) used odha is joining social support groups , open hiv status , counseling and improving the optimization of adherence to art is the joint responsibility of of the program , patients , health care providers , and family and community projects